An Edinburgh Eleven: Pencil Portraits from College Life - Barrie, J. M. (James Matthew), 1860-1937 (Salt Lake City, UT : Project Gutenberg, 2012)
"An Edinburgh Eleven: Pencil Portraits from College Life" by J. M. Barrie is a collection of literary sketches written in the late 19th century. This work offers a delightful exploration of life at Edinburgh University, capturing the essence of both notable figures and everyday experiences through witty and insightful reflections. The book features portraits of several prominent personalities from Barrie's time, including politicians and professors, revealing not only their public personas but also their quirks and idiosyncrasies as perceived by the author. The opening of the work introduces Lord Rosebery, a prominent political figure, through a blend of humor and keen observations. The narrator recounts a personal anecdote about their first encounter with Lord Rosebery during their student days, detailing the amusing mishaps and misunderstandings that characterize the ambitious politician's life. The style is conversational and engaging, as Barrie employs anecdotes, historical references, and playful commentary to breathe life into the portrayal of not just Rosebery, but the vibrant atmosphere of student life and academia at Edinburgh during the author's youth. The chapters promise a similar blend of wit and insight as they progress through other prominent figures and experiences, inviting readers into a personal and entertaining view of college life. (This is an automatically generated summary.)
Lord Rosebery -- Professor Masson -- Professor Blackie -- Professor Calderwood -- Professor Tait -- Professor Fraser -- Professor Chrystal -- Professor Sellar -- Mr. Joseph Thomson -- Robert Louis Stevenson -- Rev. Walter C. Smith, D.D.
Release date is 2012-03-19
E-text prepared by David Edwards, Diane Monico, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://www.archive.org)
Keywords: University of Edinburgh -- Biography